Re-viewing fascism : Italian cinema, 1922-1943 - Reich, Jacqueline, 1965-; Garofalo, Piero (Bloomington : Indiana University Press, 2002)
When Benito Mussolini proclaimed that "Cinema is the strongest weapon," he was telling only half the story. In reality, very few feature films during the Fascist period can be labeled as propaganda. Re-viewing Fascism considers the many films that failed as "weapons" in creating cultural consensus and instead came to reflect the complexities and contradictions of Fascist culture. The volume also examines the connection between cinema of the Fascist period and neorealism -- ties that many scholars previous
Mussolini at the movies : fascism, film, and culture / Jacqueline Reich -- Dubbing l'arte muta : poetic layerings around Italian cinema's transition to sound / Giorgio Bertellini -- Intimations of neo-realism in the fascist Ventennio / ennio di Nolfo -- Placing cinema, fascism, and the nation in a diagram of Italian modernity / James Hay -- Sex in the cinema : regulation and transgression in Italian films, 1930-1943 / David Forgacs -- Luchino Visconti's (homosexual) Ossessione / William Van Watson -- Ways of looking in black and white : female spectatorship and the miscege-national body in Sotto la croce del sud / Robin Pickering-Iazzi -- Seeing red : the Soviet influence on Italian cinema in the thirties / Piero Garofalo -- Theatricality and impersonation : the politics of style in the cinema of the Italian fascist era / Marcia Landy -- Shopping for autarchy : fascism and reproductive fantasy in Mario Camerini's Grandi magazzini / Barbara Spackman -- The last film festival : the Venice Biennale goes to war / Marla Stone -- Film stars and society in fascist Italy / Stephen Gundle.
Includes bibliographical references (pages 341-351) and index.
Print version record.
JSTOR
Keywords: Motion pictures -- Italy -- History; Fascism and motion pictures -- Italy -- History; Cinéma -- Italie -- Histoire; Fascisme et cinéma -- Italie -- Histoire; PERFORMING ARTS -- Film & Video -- Reference; PERFORMING ARTS -- Film & Video -- General; Fascism and motion pictures; Motion pictures; Italy; Filmkunst; Fascisme; Italië; History